Grain-oriented electrical steel sheet
By incorporating grooves and an intermediate SiO layer in the manufacturing process of directional electromagnetic steel sheets, the challenges of achieving heat-resistant magnetic domain control and low iron loss without a forsterite coating are addressed, resulting in improved magnetic properties and reduced iron loss.
Patent Information
- Application Number
- JP2024529850
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-11-01
- Filing Date
- 2023-11-01
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2043-11-01
AI Technical Summary
Directional electromagnetic steel sheets without a forsterite coating face challenges in achieving heat-resistant magnetic domain control and maintaining low iron loss, as they often require non-heat-resistant magnetic domain control methods that are not suitable for all transformer manufacturing processes.
The manufacturing process involves creating directional electromagnetic steel sheets with a plurality of grooves on their surface and an intermediate SiO layer, which allows for the formation of a high-tensile insulating coating without a forsterite coating. This configuration enhances adhesion and reduces iron loss.
This method enables the production of directional electromagnetic steel sheets with excellent magnetic properties and reduced iron loss, even without a forsterite coating, thereby improving their performance and versatility in transformer applications.
Smart Images

Figure 0007656247000004 
Figure 0007656247000005 
Figure 0007656247000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a grain-oriented electrical steel sheet. [Background technology]
[0002] Grain-oriented electrical steel sheets are mainly used in transformers. Since transformers are continuously excited and generate energy loss over a long period from installation to disposal, the energy loss when magnetized with AC, that is, core loss, is the main index that determines the value of a transformer.
[0003] Many methods have been proposed to reduce the iron loss of grain-oriented electrical steel sheets. For example, the Goss orientation in the steel sheet structure, {110} <001> These include techniques to increase the concentration in a certain orientation, techniques to increase the content of solid solution elements such as Si which increases the electrical resistance of steel sheets, and techniques to reduce the thickness of steel sheets.
[0004] It is also known that applying tension to steel sheets is an effective method for reducing iron loss. Therefore, a coating is usually formed on the surface of grain-oriented electrical steel sheets in order to reduce iron loss. This coating applies tension to the grain-oriented electrical steel sheets, thereby reducing the iron loss of each steel sheet. This coating further ensures electrical insulation between the steel sheets when the grain-oriented electrical steel sheets are stacked for use, thereby reducing the iron loss of the steel core.
[0005] An example of a grain-oriented electrical steel sheet having a coating is one in which a forsterite coating, which is an oxide coating containing Mg, is formed on the surface of a base steel sheet, and an insulating coating is further formed on the surface of the forsterite coating (hereinafter also referred to as a glass coating). That is, in this case, the coating on the base steel sheet includes a forsterite coating and an insulating coating (hereinafter also referred to as a tension coating). The forsterite coating and the insulating coating each perform both an insulating function and a function of applying tension to the base steel sheet.
[0006] The forsterite coating is an oxide coating containing Mg, and is formed during the finish annealing process, which causes secondary recrystallization in the steel sheet, by a reaction between an annealing separator mainly composed of magnesia (MgO) and silicon oxide (SiO2) formed on the base steel sheet during decarburization annealing, during heat treatment at 900 to 1200°C for 30 hours or more.
[0007] The insulating coating is formed by applying a coating solution containing, for example, phosphoric acid or a phosphate, colloidal silica, or chromic anhydride or a chromate to the base steel sheet after finish annealing, and drying it at 300 to 950°C for 10 seconds or more.
[0008] In order for an insulating coating to exert its insulating function and its function of applying tension to the base steel sheet, high adhesion is required between the coating and the base steel sheet.
[0009] Conventionally, the adhesion between the insulating coating and the steel sheet has been ensured mainly by the anchor effect caused by the unevenness of the interface between the base steel sheet and the forsterite coating. However, in recent years, it has become clear that the unevenness of the interface also hinders the movement of domain walls when the grain-oriented electrical steel sheet is magnetized, and is therefore also a factor preventing low iron loss.
[0010] Therefore, in order to further reduce iron loss, a technology has been proposed that ensures the adhesion of the insulating coating while smoothing the above-mentioned interface, without the presence of the forsterite coating, which is an oxide coating containing Mg. For example, Patent Document 1 proposes a technique in which the forsterite film is removed by pickling or the like, the surface of the base steel sheet is smoothed by chemical polishing or electrolytic polishing, and then a thin metal plating is applied to the surface. Patent Document 2 proposes a technique in which an annealing separator containing alumina (Al2O3) is used during finish annealing to suppress the formation of the forsterite film itself and smooth the surface of the base steel sheet.
[0011] However, grain-oriented electrical steel sheets without a forsterite film may sacrifice core loss unless they are subjected to non-heat-resistant domain control such as distortion by laser or electron beam irradiation. On the other hand, even if non-heat-resistant domain control such as distortion by laser or electron beam irradiation is performed, they cannot be used as materials for wound core transformers that require annealing in the transformer manufacturing process.
[0012] Therefore, the application of heat-resistant magnetic domain control by pressing has been proposed in Patent Document 3. However, if there is no forsterite film, this may affect the shape of the steel sheet after magnetic domain control (after pressing).
[0013] Furthermore, even if a tension coating is applied to a grain-oriented electrical steel sheet that does not have a forsterite coating, the total coating tension is small because the steel sheet does not have a forsterite coating. If the coating tension is small, the effect of improving iron loss is small even if heat-resistant magnetic domain control is performed by pressing or the like, so that the grain-oriented electrical steel sheet that does not have a forsterite coating is inferior in terms of iron loss to a grain-oriented electrical steel sheet that has a forsterite coating. [Prior art documents] [Patent documents]
[0014] [Patent Document 1] Japanese Patent Application Publication No. 49-096920 [Patent Document 2] International Publication No. 2002 / 088403 [Patent Document 3] Special Publication No. 62-053579 [Patent Document 4] International Publication No. 2020 / 149321 Summary of the Invention [Problem to be solved by the invention]
[0015] The present invention has been made in consideration of the above problems, and has an object to provide a grain-oriented electrical steel sheet that does not have a forsterite coating and has heat-resistant magnetic domain control, and that has an objective of improving iron loss and has excellent iron loss. [Means for solving the problem]
[0016] The present inventors have conducted extensive research to solve the above problems. As a result, they have found that by devising a steel sheet manufacturing process, it is possible to manufacture a grain-oriented electrical steel sheet that is excellent in core loss and steel sheet shape even without a forsterite coating. The present invention has been made based on the above findings, and the gist of the present invention is as follows.
[0017] [1] The grain-oriented electrical steel sheet according to one embodiment of the present invention has a plurality of grooves on its surface, and has an SiO2 intermediate layer and an insulating coating, in that order, on the surface of a steel sheet serving as a base material, the insulating coating having a coating tension of 10 MPa or more, and does not have a forsterite coating. [2] The grain-oriented electrical steel sheet according to [1], wherein the absolute value of the angle θ between the longitudinal direction of the groove and a direction perpendicular to the rolling direction and the sheet thickness direction is 0 to 40°, the width W of the groove is 20 to 300 μm, the depth D of the groove is 10 to 50 μm, and the spacing P of the groove in the rolling direction is 1 to 30 mm. [3] The grain-oriented electrical steel sheet according to the above [1] or [2], which has an SiO2 internal oxidation layer immediately beneath the surface of the steel sheet serving as the base material. [4] The grain-oriented electrical steel sheet according to any one of the above [1] to [3], wherein in a cross section in the sheet thickness direction of the steel sheet, the unevenness height at the interface between the SiO2 internal oxidation layer and the steel sheet serving as the base material is 0.001 μm or more and 0.100 μm or less in the sheet thickness direction of the steel sheet. [5] The grain-oriented electrical steel sheet according to any one of the above [1] to [4], wherein the grooves are formed by etching or laser. Effect of the Invention
[0018] According to the present invention, a method for producing a grain-oriented electrical steel sheet that does not have a forsterite film and has excellent magnetic properties can be provided. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a schematic diagram of an electromagnetic steel sheet in which grooves are formed. [Diagram 2] FIG. 2 is a cross-section in the sheet thickness direction (cross-section perpendicular to the steel sheet surface) of the electromagnetic steel sheet according to the present invention, and is a schematic diagram for explaining the coating structure of the electromagnetic steel sheet. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, the present invention will be described using as an example a grain-oriented electrical steel sheet according to one embodiment of the present invention (hereinafter, referred to as the present electrical steel sheet).
[0021] <Insulation coating tension> Although the present electrical steel sheet does not have a base steel sheet having a plurality of grooves on its surface and a forsterite coating (glass coating) on the surface of the base steel sheet, an insulating coating can be obtained with a tension of 10 MPa or more, and good core loss properties can be obtained. The tension of the insulating coating is preferably 11 MPa or more, 12 MPa or more, 13 MPa or more, 14 MPa or more, or 15 MPa or more. The tension of the insulating coating can be measured, for example, by cutting the electromagnetic steel sheet to 30 x 300 mm, removing the insulating coating on one side, fixing one end of the steel sheet (either short side) and measuring the warping of the steel sheet, and then calculating the tension from the following formula (1). σ=1.39×t×χ / T Equation (1) σ: Insulation coating tension (MPa) t: Plate thickness after removing coating from one side (mm) T: Plate thickness before removing coating from one side (mm) χ: Warpage (mm)
[0022] The components of the insulating film are not particularly limited, but it is preferable to form a film by applying an aqueous coating solution (insulating film forming solution) mainly composed of phosphate and colloidal silica. As the phosphate, for example, phosphates of Ca, Al, Sr, etc. are preferable, and among them, aluminum phosphate salt is more preferable. The type of colloidal silica is not particularly limited, and its particle size (average particle size) can also be appropriately selected. However, if the particle size exceeds 200 nm, it may settle in the treatment solution, so the particle size (average particle size based on the number) of colloidal silica is preferably 200 nm or less, more preferably 190 nm or less, 180 nm or less, or 170 nm or less. The film thickness of the insulating film is not particularly limited. However, since it is difficult for tension to occur when the film thickness is thin, the film thickness is preferably 3 μm or more, more preferably 4 μm or more, 5 μm or more, or 6 μm or more. On the other hand, if the film thickness is too thick, the proportion of the non-magnetic layer in the steel sheet increases, and deterioration of iron loss due to a decrease in magnetic flux density occurs, so the film thickness is preferably 30 μm or less, more preferably 25 μm or less, or 20 μm or less.
[0023] <SiO2 intermediate layer> It is difficult to form a high-tension insulating film on an electromagnetic steel sheet that does not have a glass film that plays an anchoring role for the insulating film on the steel sheet surface. The inventors of the present invention have found that a high-tension insulating film can be formed by appropriately controlling the baking atmosphere of the insulating film. Although the mechanism is not clear, it is considered that an intermediate layer of SiO2 (SiO2 intermediate layer) is formed during the baking and annealing of the insulating film, and it plays an anchoring role, so that the insulating film adheres closely and high tension can be achieved.
[0024] As shown in Fig. 2, the cross-section of the electromagnetic steel sheet 1 according to the present invention is composed of a steel sheet 10 as a base material, a SiO2 internal oxidation layer 11 immediately below the surface of the base material steel sheet, a SiO2 intermediate layer 12 on the surface of the base material steel sheet, and an insulating film 13 thereon in this order. Since the lattice constants of the base material steel sheet and SiO2 are close, the lattice matching is good. There is an internally oxidized SiO2 (SiO2 internal oxidation layer 11) generated by finish annealing on the surface of the base material steel sheet 10, and a SiO2 intermediate layer 12 is formed thereon. Therefore, it is considered that the crystal structure becomes stable. Further, the insulating film 13 has SiO2 as a main component, and since this is formed on the SiO2 intermediate layer 12, the crystal structure also becomes stable. Therefore, the presence of the SiO2 intermediate layer 12 is considered to produce a stronger bonding state 1 than when the steel sheet and the insulating film 13 are in direct contact, and as a result, the high tension of the insulating film can be obtained. The SiO2 intermediate layer 12 can be confirmed by observing the cross-section in the thickness direction of the electromagnetic steel sheet on which the insulating film 13 is formed.
[0025] <SiO2 internal oxidation layer> When a SiO2 internal oxidation layer 11 is formed on the surface of the electromagnetic steel sheet 10 having no glass film, and a SiO2 intermediate layer 12 and a high-tension insulating film 13 are formed thereon, it becomes possible to make the adhesion between the insulating film and the steel sheet stronger. Although the mechanism by which the adhesion becomes stronger has not been clarified, since the SiO2 internal oxidation layer 11 is formed with minute irregularities on the steel sheet surface, it is considered that the anchor effect of the SiO2 intermediate layer is further enhanced.
[0026] The SiO2 internal oxidation layer and the uneven structure of the steel sheet surface can be confirmed by TEM observation of the sheet thickness cross section (cross section perpendicular to the steel sheet surface) of the electrical steel sheet on which an insulating coating has been formed. The surface position of the base steel sheet 10 can be confirmed by EDS analysis and contrast in bright field images, and the SiO2 internal oxidation layer directly below the surface of the base steel sheet can be confirmed. In a TEM image of the steel sheet thickness cross section, the interface between the base steel sheet and the SiO2 internal oxidation layer (which appears curved in the cross section, so this curve is called the interface curve) is identified. The uneven structure of the SiO2 internal oxidation layer and the steel sheet surface can be evaluated by the unevenness of this interface. Explaining with reference to Fig. 2, in an arbitrarily selected observation surface of 1 µm width, the uneven structure of the SiO2 internal oxidation layer and the steel sheet surface can be evaluated by measuring the distance (called unevenness height 14) between a line 16 connecting the tip of an interface curve 15 between a base steel sheet 10 and an SiO2 internal oxidation layer 11 on the steel sheet surface side, and a line 17 connecting the tip of the interface curve 15 on the steel sheet center side. If the line 16 connecting the tip of the interface curve 15 on the steel sheet surface side and the line 17 connecting the tip of the interface curve 15 on the steel sheet center side are not parallel, the arithmetic average value of the distances at both ends of the line (both ends of the 1 µm wide observation surface) may be taken as the distance between the two lines (unevenness height 14).
[0027] The uneven structure (unevenness height) of the SiO2 internal oxidation layer and the steel sheet surface is preferably 0.001 μm or more and 0.100 μm or less. If the uneven structure (unevenness height) of the SiO2 internal oxidation layer and the steel sheet surface is too shallow, the effect of strengthening the adhesion of the insulating coating due to the formation of the internal oxidation layer cannot be obtained, so the uneven structure (unevenness height) is preferably 0.001 μm or more, more preferably 0.003 μm or more, 0.005 μm or more, 0.010 μm or more, or 0.020 μm or more. If the uneven structure (unevenness height) of the SiO2 internal oxidation layer and the steel sheet surface is too deep, iron loss deteriorates, so it is preferably 0.100 μm or less, more preferably 0.095 μm or less, 0.090 μm or less, 0.085 μm or less, or 0.080 μm or less.
[0028] <<Grooves on the steel plate surface>> As shown in Fig. 1, on the surface of the base steel sheet, multiple grooves are formed adjacent to each other in the rolling direction of the base steel sheet. The groove direction (angle θ), groove width W, depth D, and interval P are determined taking into account iron loss, as in the case of ordinary grain-oriented electrical steel sheets.
[0029] <Angle θ between the longitudinal direction of the base steel plate and the longitudinal direction of the groove> The angle θ between the direction perpendicular to the rolling direction and thickness direction of the base steel sheet (sheet width direction) and the longitudinal direction of the groove is set to 40° or less, because if it is too large, there will be no magnetic domain control effect and the iron loss improvement effect will not be obtained. A smaller angle θ is preferable, and it is recommended to set it to 35° or less, 30° or less, 25° or less, 20° or less, 15° or less, 10° or less, 8° or less, 6° or less, or 5° or less. The lower limit of the angle θ is 0°, that is, when the longitudinal direction of the groove is parallel to the sheet width direction. The direction of the angle θ is not important, and refers to the acute angle between the longitudinal direction of the groove and the sheet width direction. Multiple grooves are arranged roughly parallel to each other on the surface of the base steel sheet, and the angle θ for each groove may be within the range described above.
[0030] <Groove width W> The groove width W refers to the width of the groove on the surface of the base steel sheet in the cross section of the groove (groove cross section) on a plane perpendicular to the longitudinal direction of the groove. If the groove width W is too narrow, it will not become the starting point of magnetic pole generation, there will be no magnetic domain control effect, and good iron loss will not be obtained, so it is preferable to set it to 20 μm or more. On the other hand, if it is too wide, it will not become the starting point of magnetic pole generation, there will be no magnetic domain control effect, only the magnetic flux density will be significantly reduced, and good iron loss will not be obtained, so it is preferable to set it to 300 μm or less. The lower limit of the groove width W is preferably 25 μm, 30 μm, or 35 μm. The upper limit of the groove width W is preferably 250 μm, 200 μm, 150 μm, 100 μm, or 80 μm.
[0031] <Groove depth D> If the groove depth D is too shallow, it will not become the starting point of the magnetic pole, there will be no magnetic domain control effect, and good iron loss will not be obtained, so it is recommended to set it to 10 μm or more. On the other hand, if it is too deep, the magnetic domain control effect will reach saturation, and only the magnetic flux density will drop significantly, so good iron loss will not be obtained, so it is recommended to set it to 40 μm or less. The lower limit of the groove depth D is preferably 11 μm, 12 μm, 13 μm, 14 μm, or 15 μm. The upper limit of the groove depth D is preferably 38 μm, 36 μm, 34 μm, 32 μm, 30 μm, 28 μm, or 26 μm.
[0032] <Groove Spacing P> The groove spacing P is the distance between the longitudinal centerlines of adjacent grooves arranged approximately parallel to each other on the surface of the base steel sheet, and refers to the distance in the rolling direction of the base steel sheet. The centerline of the groove is a line parallel to the longitudinal direction of the groove that passes through the midpoint of the groove on the surface of the base steel sheet in the groove cross section. If the groove spacing P is too narrow, the magnetic domain control effect is saturated and only the magnetic flux density is significantly reduced, so good iron loss cannot be obtained, so it is preferable to set it to 1 mm or more. On the other hand, if it is too wide, the magnetic domain control effect is not sufficiently obtained and good iron loss cannot be obtained, so it is preferable to set it to 30 mm or less. The groove spacing P does not have to be equal, but the groove spacing P between adjacent grooves should be within the above range. The lower limit of the groove spacing P is preferably 1.2 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.8 mm, or 2.0 mm. The upper limit of the groove spacing P is preferably 25.0 mm, 20.0 mm, 15.0 mm, 10.0 mm, 7.0 mm, or 5.0 mm.
[0033] <<Manufacturing method>> An example of a manufacturing method of the present electromagnetic steel sheet will be described. First, a cold-rolled steel sheet for the present electromagnetic steel sheet is manufactured by a known method. The steel sheet components and the manufacturing method of the cold-rolled steel sheet are not particularly limited, and known methods, such as the steel sheet components and steel sheet manufacturing method described in Patent Document 4, can be adopted. An example of a specific process is shown below, but the present invention is not limited to this example process.
[0034] (i) A hot rolling process in which a steel billet having a specified chemical composition is hot rolled to obtain a hot rolled steel sheet. If necessary, the method may include a hot-rolled sheet annealing step of annealing the hot-rolled steel sheet, and a hot-rolled sheet pickling step of pickling the hot-rolled steel sheet or the hot-rolled annealed steel sheet. (ii) a cold rolling step in which the hot-rolled steel sheet is cold-rolled once or twice or more with intermediate annealing to obtain a cold-rolled steel sheet; (iii) a decarburization annealing step in which the cold-rolled steel sheet is subjected to decarburization annealing and, if necessary, nitriding treatment to obtain a decarburization annealed sheet; (iv) an annealing separator application step of applying an annealing separator to the decarburized annealed sheet and drying it; (v) a finish annealing step in which the decarburized annealed sheet to which the annealing separator has been applied is subjected to finish annealing to obtain a finish annealed steel sheet; (vi) An annealing separator removal step of removing excess annealing separator from the surface of the finish annealed steel sheet by a method including one or both of water washing and pickling. (vii) An insulating coating forming step of forming an insulating coating on the surface of the finish annealed steel sheet (viii) A magnetic domain control process for performing magnetic domain control processing The magnetic domain control process involves forming grooves on the surface of the steel sheet, and can be carried out on steel sheet after cold rolling, decarburization annealing, decarbonitriding annealing or finish annealing, or on steel sheet to which a tension coating has been further applied.
[0035] <Steel plate components> As described above, the steel sheet components are not particularly limited. As described above, for example, the steel sheet components described in Patent Document 4 may be adopted. In addition, for example, in the case of a hot-rolled steel sheet, a steel sheet containing, in mass%, C: 0.030-0.100%, Si: 0.80-7.00%, Mn: 0.01-1.00%, S+Se: 0.060% or less, acid-soluble Al: 0.010-0.065%, N: 0.004-0.012% or less, with the balance being Fe and impurities may be adopted. In this case, the reason for limiting the chemical composition of the steel slab will be explained. Hereinafter, unless otherwise specified, "%" regarding the chemical composition means mass%.
[0036] [C:0.030~0.100%] C (carbon) is an element effective in controlling the primary recrystallization structure, but has a negative effect on magnetic properties, so it is an element that is removed by decarburization annealing before final annealing. If the C content of a steel slab is high, the decarburization annealing time will be long and productivity will decrease, so the C content should be 0.100% or less. It is preferably 0.085% or less, and more preferably 0.070% or less. A low C content is preferable, and there are no particular limitations on the C content. However, when considering the productivity in industrial production and the magnetic properties of the product, the practical lower limit of the C content should be set to 0.030%.
[0037] [Si:0.80~7.00%] Silicon (Si) increases the electrical resistance of steel sheets and reduces iron loss. If the Si content is low, γ (austenite) transformation occurs during final annealing, damaging the crystal orientation of the grain-oriented electrical steel sheet, so the Si content should be 0.80% or more. The Si content is preferably 1.00% or more, 1.50% or more, 2.00% or more, and more preferably 2.50% or more. On the other hand, if the Si content is high, cold workability is reduced and cracks are likely to occur during cold rolling, so the Si content is preferably 7.00% or less, and is preferably 6.50% or less, 5.00% or less, 4.50% or less, and more preferably 4.00% or less.
[0038] [Mn: 0.01-1.00%] Manganese (Mn) also increases the electrical resistance of the steel sheet and reduces iron loss. Mn also combines with S or Se to produce MnS or MnSe, which functions as an inhibitor. If the Mn content is too low or too high, secondary recrystallization is not stable, so the Mn content should be 0.01% or more and 1.00% or less. The preferred lower limit of the Mn content is 0.03%, 0.05%, or 0.08%, and more preferably 0.09%. The preferred upper limit of the Mn content is 0.80%, 0.50%, 0.30%, or 0.20%.
[0039] [S and / or Se total: 0.060% or less] S (sulfur) and Se (selenium) combine with Mn to form MnS and / or MnSe, and function as inhibitors. If the total content of S and Se (S+Se) is high, the precipitation and dispersion of MnS and MnSe becomes non-uniform after hot rolling. In this case, the desired secondary recrystallization structure is not obtained, the magnetic flux density decreases, or MnS remains after purification, causing deterioration of hysteresis loss. Therefore, the total content of S and Se is preferably 0.060% or less. There is no particular lower limit, and it does not have to be included (0%), but in order to reliably obtain the effect, it is preferably 0.003% or more, 0.005% or more, 0.010% or more, or 0.015% or more.
[0040] [Acid-soluble Al (Sol.Al): 0.010~0.065%] Acid-soluble Al (aluminum) (Sol.Al) combines with N to form AlN or (Al,Si)N, and functions as an inhibitor. If the amount of acid-soluble Al is small, the effect is not fully expressed and secondary recrystallization does not proceed sufficiently, so the acid-soluble Al content is preferably 0.010% or more. The acid-soluble Al content is preferably 0.015% or more, more preferably 0.020% or more. On the other hand, if the acid-soluble Al content is large, the precipitation dispersion of AlN or (Al,Si)N becomes non-uniform, the required secondary recrystallization structure is not obtained, and the magnetic flux density decreases, so the acid-soluble Al (Sol.Al) is preferably 0.065% or less. The acid-soluble Al is preferably 0.055% or less, more preferably 0.050% or less.
[0041] [N:0.004~0.012%] N (nitrogen) combines with Al to form AlN or (Al, Si)N, and functions as an inhibitor. If the N content is low, the formation of AlN or (Al, Si)N becomes insufficient, so N is set to 0.004% or more. It is preferably set to 0.005% or more, 0.006% or more, or 0.007% or more. On the other hand, if the N content is high, there is a concern that blisters (voids) may be formed in the steel sheet, so the N content is set to 0.012% or less.
[0042] [Cr:0% or more and 0.30% or less] Cr (chromium) does not have to be contained, but like Si, it is an effective element for increasing electrical resistance and reducing iron loss. Therefore, Cr may be contained, and in order to reliably obtain the effect, the Cr content is preferably 0.02% or more, and more preferably 0.05% or more. On the other hand, if the Cr content is too high, a decrease in magnetic flux density becomes a problem, so the upper limit of the Cr content should be 0.30%, and preferably 0.20% or 0.12%.
[0043] [Cu:0% or more and 0.40% or less] Although Cu (copper) is not necessarily contained, it is an effective element for increasing electrical resistance and reducing iron loss. Therefore, it may be contained, and in order to reliably obtain the effect, the Cu content is preferably 0.05% or more, and more preferably 0.10% or more. On the other hand, if the Cu content is too high, the iron loss reduction effect becomes saturated and it may cause surface defects called "copper scuffs" during hot rolling. Therefore, the upper limit of the Cu content is preferably 0.40%, more preferably 0.30% or 0.20%.
[0044] [P: 0% or more and 0.50% or less] Although P (phosphorus) is not necessarily contained, it is an effective element for increasing electrical resistance and reducing iron loss. Therefore, it may be contained, and in order to reliably obtain the effect, the P content is preferably 0.005% or more, and more preferably 0.010% or more. On the other hand, if the P content is high, problems may occur in the rollability, so the upper limit of the P content is preferably 0.50%, and more preferably 0.20% or 0.15%.
[0045] [Sn: 0% or more and 0.30% or less] [Sb: 0% or more and 0.30% or less] Sn (tin) and Sb (antimony) are not necessarily contained, but they stabilize the secondary recrystallization and form the Goss orientation ({110} <001> Sn is an effective element for developing the grain orientation. Therefore, Sn may be contained, and in order to reliably obtain the effect, the Sn content is 0.02% or more, preferably 0.05% or more, and the Sb content is 0.01% or more, preferably 0.03% or more. On the other hand, too much Sn or Sb may adversely affect the magnetic properties, so the upper limit of the Sn content and the Sb content is preferably 0.30%, and more preferably 0.15% or 0.10%, respectively.
[0046] [Ni: 0% or more and 1.00% or less] Although Ni (nickel) is not necessarily contained, it is an effective element for increasing electrical resistance and reducing iron loss. Ni is also an effective element for controlling the metal structure of the hot-rolled steel sheet and improving the magnetic properties. Therefore, Ni may be contained, and in order to reliably obtain the effect, the Ni content is preferably 0.01% or more, and more preferably 0.02% or more. On the other hand, if the Ni content is high, the secondary recrystallization may become unstable, so the Ni content should be 1.00% or less, preferably 0.20% or less, or 0.10% or less.
[0047] [B: 0% or more and 0.008% or less] Although B (boron) does not have to be contained, it bonds with N to form BN and exerts an inhibitor effect. Therefore, if it is allowed to be contained and the effect is reliably obtained, the B content is preferably 0.0005% or more, and more preferably 0.001% or more. On the other hand, if the B content is too high, there is a concern that it may have an adverse effect on the magnetic properties, so the upper limit of the B content is preferably 0.008%, and more preferably 0.005% or 0.003%.
[0048] [V:0% or more and 0.15% or less] [Nb: 0% or more and 0.20% or less] [Ti: 0% or more and 0.015% or less] Although V (vanadium), Nb (niobium), and Ti (titanium) are not necessarily contained, they are elements that combine with N and C to function as inhibitors. Therefore, they may be contained, and in order to reliably obtain these effects, the V content is preferably 0.002% or more, and more preferably 0.010% or more. The Nb content is preferably 0.005% or more, and more preferably 0.020% or more. The Ti content is preferably 0.002% or more, and more preferably 0.004% or more. On the other hand, if the content of V, Nb, or Ti is high, the magnetic properties of the final product (electromagnetic steel sheet) may deteriorate. Therefore, the upper limit of the V content is preferably 0.150%, and more preferably 0.100% or 0.050%. The upper limit of the Ti content is preferably 0.0150%, and more preferably 0.010% or 0.008%. The upper limit of the Nb content is preferably 0.200%, and more preferably 0.100% or 0.080%.
[0049] [Mo: 0% or more and 0.10% or less] Mo (molybdenum) is not necessarily contained, but it is an effective element for increasing electrical resistance and reducing iron loss. Therefore, it may be contained, and in order to reliably obtain the effect, the Mo content is preferably 0.005% or more, and more preferably 0.01% or more. On the other hand, if the Mo content is high, problems may arise in the rollability of the steel sheet, so the upper limit of the Mo content is preferably 0.10%, and more preferably 0.08% or 0.05%.
[0050] [Bi:0% or more and 0.010% or less] Bi (bismuth) is not necessarily contained, but it is an effective element for stabilizing precipitates such as sulfides and enhancing the function as an inhibitor. Therefore, it may be contained, and in order to reliably obtain the effect, the Bi content is preferably 0.001% or more, and more preferably 0.002% or more. On the other hand, a high Bi content can adversely affect the magnetic properties, so the upper limit of the Bi content is preferably 0.010%, and more preferably 0.008% or 0.006%.
[0051] The balance other than the above elements is Fe and impurities. Here, "impurities" refers to components that are mixed in due to various factors in raw materials such as ores and scraps and manufacturing processes during industrial production of steel, and are permissible within a range that does not adversely affect the present invention.
[0052] <Manufacturing method> Next, a method for producing an electrical steel sheet according to the present invention will be described with reference to an embodiment, but the method for producing an electrical steel sheet according to the present invention is not limited to the embodiment described here.
[0053] <Hot rolling process> There is no limitation on the method for producing the steel billet (slab) to be subjected to the hot rolling process. For example, molten steel having a predetermined chemical composition may be produced, and the molten steel may be used to produce the slab. The slab may be produced by a continuous casting method, or the molten steel may be used to produce an ingot, and the ingot may be subjected to blooming to produce the slab. Alternatively, the slab may be produced by other methods. The thickness of the slab is not particularly limited, but is, for example, 150 to 350 mm. The thickness of the slab is preferably 220 to 280 mm. As the slab, a so-called thin slab having a thickness of 10 to 70 mm may be used.
[0054] Next, the conditions for hot rolling the above-mentioned steel slab will be described. The hot rolling conditions are not particularly limited. For example, the following conditions are used. The slab is heated prior to hot rolling. The slab is charged into a known heating furnace or known soaking furnace and heated. As one method, the slab is heated to 1100°C or more and 1280°C or less. By setting the heating temperature of the slab to 1280°C or less, it is possible to avoid various problems (such as the need for a dedicated heating furnace and a large amount of molten scale) that occur when the slab is heated at a temperature higher than 1280°C. If the heating temperature is too low, hot rolling may become difficult and productivity may decrease. Therefore, the heating temperature may be set in the range of 1280°C or less, taking productivity into consideration. The preferable lower limit of the heating temperature of the slab is 1100°C. The preferable upper limit of the heating temperature of the slab is 1250°C.
[0055] Alternatively, the slab may be heated to a high temperature of 1320°C or higher. By heating to a high temperature of 1320°C or higher, AlN and Mn(S,Se) are dissolved and finely precipitated in the subsequent process, allowing secondary recrystallization to occur stably. In this case, the upper limit temperature is 1350°C, at which the slab melts.
[0056] It is also possible to omit the slab heating step itself and start hot rolling before the temperature of the slab drops to a predetermined temperature after casting.
[0057] Next, hot rolling is performed on the heated slab. The hot rolling mill includes, for example, a roughing mill and a finishing mill arranged downstream of the roughing mill. The roughing mill includes roughing stands arranged in a row. Each roughing stand includes a plurality of rolls arranged vertically. The finishing mill also includes finishing stands arranged in a row. Each finishing stand includes a plurality of rolls arranged vertically. The heated steel material is rolled by the roughing mill, and then further rolled by the finishing mill to produce a hot-rolled steel sheet. The finishing temperature in the hot rolling process (the steel sheet temperature at the exit side of the finishing rolling stand that finally rolls down the steel sheet in the finishing mill) is, for example, 700 to 1150°C. The above hot rolling process produces a hot-rolled steel sheet.
[0058] <Hot-rolled sheet annealing process> In the hot-rolled sheet annealing step, the hot-rolled steel sheet obtained in the hot rolling step is annealed (hot-rolled sheet annealing) as necessary to obtain a hot-rolled annealed sheet. The purpose of hot-rolled sheet annealing is to homogenize the non-uniform structure generated during hot rolling as much as possible, to control the precipitation of AlN as an inhibitor (fine precipitation), and to control the second phase / solubilized carbon. The annealing conditions may be selected from known conditions according to the purpose. For example, when homogenizing the non-uniform structure generated during hot rolling, the hot-rolled steel sheet may be held at an annealing temperature (furnace temperature in a hot-rolled sheet annealing furnace) of 750 to 1200°C for 30 to 600 seconds. Hot-rolled sheet annealing is not necessarily required, and whether or not to perform the hot-rolled sheet annealing step may be determined depending on the properties required of the grain-oriented electrical steel sheet to be finally manufactured and the manufacturing costs.
[0059] <Hot rolled plate pickling process> In the hot-rolled steel sheet pickling process, the hot-rolled steel sheet after the hot-rolling process or the hot-rolled annealed steel sheet after the hot-rolled steel sheet annealing process is pickled as necessary to remove scale formed on the surface. The pickling conditions are not particularly limited, and may be performed under known conditions.
[0060] <Cold rolling process> In the cold rolling process, the hot-rolled steel sheet or the hot-rolled annealed sheet after the hot rolling process, the hot-rolled sheet annealing process, or the hot-rolled sheet pickling process is subjected to cold rolling once or two or more times with intermediate annealing to obtain a cold-rolled steel sheet. The cold rolling reduction in the final cold rolling is preferably 80% or more, more preferably 90% or more. The upper limit of the cold rolling reduction is preferably 95%. Here, the cold rolling reduction ratio (%) is defined as follows: Cold rolling ratio (%) = (1 - thickness of steel plate after cold rolling / thickness of steel plate before cold rolling) x 100
[0061] <Decarburization annealing process> In the decarburization annealing process, the cold-rolled steel sheet produced in the cold rolling process is subjected to decarburization annealing to cause primary recrystallization. In the decarburization annealing, the oxidation degree (PH2O / PH2: partial pressure ratio of water vapor to hydrogen) in the annealing atmosphere (furnace atmosphere) is set to 0.01 to 0.15, and the annealing temperature is set to 750 to 900° C., and the material is held for 10 to 600 seconds. If the degree of oxidation (PH2O / PH2) is too small, not only will the decarburization speed slow down and productivity decrease, but decarburization will be insufficient and magnetic properties will deteriorate after final annealing. On the other hand, if the degree of oxidation is too high, Fe-based oxides will be easily formed, making it difficult to smooth the interface after final annealing. Therefore, it is recommended that the degree of oxidation be 0.01 or more and 0.15 or less. If the annealing temperature is too low, not only will the decarburization rate slow down and productivity decrease, but decarburization failure will occur and magnetic properties will deteriorate after final annealing. On the other hand, if the annealing temperature is too high, the primary recrystallized grain size will exceed the desired size, and magnetic properties will deteriorate after final annealing. Therefore, the annealing temperature should be 750°C or higher and 900°C or lower. If the holding time is too short, decarburization cannot be performed sufficiently. On the other hand, if the holding time is too long, productivity decreases and the primary recrystallized grain size exceeds the desired size, resulting in deterioration of magnetic properties after final annealing. Therefore, the holding time should be 10 seconds or more and 600 seconds (10 minutes) or less.
[0062] <Nitriding treatment> In the decarburization annealing step, a nitriding treatment may be performed as necessary. By performing a nitriding treatment in the decarburization annealing step, inhibitors such as AlN and (Al,Si)N are generated before the secondary recrystallization in the finish annealing step, so that the secondary recrystallization can be stably expressed. The conditions for the nitriding treatment are not particularly limited, but it is preferable to carry out the nitriding treatment so that the nitrogen content in the vicinity of the steel sheet surface (surface layer) increases by 0.003 mass% or more, preferably 0.005 mass% or more, and more preferably 0.007 mass% or more. Since the effect is saturated when the nitrogen (N) content exceeds 0.030 mass%, the nitriding treatment may be carried out so that the nitrogen content is 0.030 mass% or less. The conditions of the nitriding treatment are not particularly limited, and may be performed under known conditions. For example, when the nitriding treatment is performed after holding the oxidation degree (PH2O / PH2) at 0.01-0.15 and at 750-900°C for 10-600 seconds, the cold-rolled steel sheet is not cooled to room temperature, but is held in an atmosphere containing ammonia during the temperature drop process to perform the nitriding treatment. It is preferable that the oxidation degree (PH2O / PH2) is in the range of 0.0001-0.01 during the temperature drop process. When the nitriding treatment is performed while holding the oxidation degree (PH2O / PH2) at 0.01-0.15 and at 750-900°C for 10-600 seconds, ammonia may be introduced into the atmospheric gas of this oxidation degree.
[0063] <Annealing separator application process> In the annealing separator application step, an annealing separator containing Al2O3 and MgO is applied to the decarburized annealed sheet, and the applied annealing separator is dried. If the annealing separator contains MgO but does not contain Al2O3, a forsterite film is formed on the steel sheet during the final annealing process. On the other hand, if the annealing separator contains Al2O3 but does not contain MgO, mullite (3Al2O3·2SiO2) is formed on the steel sheet. This mullite impedes domain wall motion and causes the magnetic properties of grain-oriented electrical steel sheets to deteriorate. Therefore, by containing Al2O3 and MgO as the annealing separator and setting the mass ratio of MgO, MgO / (MgO+Al2O3), to 5 to 50%, a forsterite coating is not formed on the steel sheet surface after finish annealing, and although a small amount of mullite is produced, it is removed in powder form in the annealing separator removal process and does not remain on the steel sheet surface, making it possible to obtain a steel sheet with a smooth surface.
[0064] If the MgO ratio MgO / (MgO+Al2O3) is too small, a large amount of mullite is formed and some of it remains on the steel sheet surface, deteriorating the iron loss, so it is set to 5% or more. Preferably, the MgO ratio MgO / (MgO+Al2O3) is 7% or more, 9% or more, or 10% or more. On the other hand, if the MgO ratio MgO / (MgO+Al2O3) is too large, forsterite is formed and deteriorating the iron loss, so it is set to 50% or less. Preferably, the MgO ratio MgO / (MgO+Al2O3) is 48% or less, 46% or less, 44% or less, 42% or less, or 40% or less.
[0065] Furthermore, if the annealing separator has too much hydrated water content, the secondary recrystallization may become unstable or the steel sheet surface may be oxidized (SiO2 is formed) during finish annealing, making it difficult to smooth the steel sheet surface. Therefore, the hydrated water content of the annealing separator is set to 1.5 mass% or less. The annealing separator is applied to the surface of the steel sheet by water slurry application, electrostatic application, etc. In the annealing separator application step, a nitride such as manganese nitride, iron nitride, or chromium nitride that decomposes before secondary recrystallization in the finish annealing step and nitrides the decarburized annealed sheet may be further added to the annealing separator.
[0066] <Finish annealing process> The decarburized annealed sheet coated with the annealing separator is then subjected to finish annealing to produce a finish annealed steel sheet. By performing finish annealing on the decarburized annealed sheet coated with the annealing separator, secondary recrystallization progresses and the crystal orientation becomes the Goss orientation ({110} <001> Accumulate in the direction (azimuth).
[0067] In the final annealing, if the furnace atmosphere contains hydrogen, the oxidation degree (PH2O / PH2) is set to 0.0001 to 0.2000, and if the atmosphere is made of an inert gas (nitrogen, argon, etc.) that does not contain hydrogen, the dew point is set to 0°C or less. This allows secondary recrystallization to occur stably and increases the degree of orientation concentration.
[0068] When hydrogen is contained in the furnace atmosphere, if the oxidation degree is too small, the dense silica film (SiO2 film) on the surface formed by decarburization annealing is reduced before the secondary recrystallization in the final annealing, making the secondary recrystallization unstable, so the oxidation degree is set to 0.0001 or more. Preferably, the oxidation degree is set to 0.0005 or more, 0.0010 or more, 0.0020 or more, or 0.0050 or more. Furthermore, in order to form an SiO2 internal oxidation layer on the steel sheet surface and further form the internal oxidation layer and the uneven structure of the steel sheet (unevenness height) to a predetermined size, the oxidation degree (PH2O / PH2) in the temperature range of 800°C to 900°C in the temperature rise process of the final annealing is set to 0.0050 or more, preferably 0.0060 or more, 0.0070 or more, 0.0080 or more, 0.0090 or more, or 0.0100 or more.
[0069] On the other hand, if the oxidation degree is too high, the decomposition of inhibitors such as AlN and (Al,Si)N is promoted, making the secondary recrystallization unstable, so the oxidation degree is set to 0.2000 or less, preferably 0.1900 or less, 0.1800 or less, 0.1700 or less, 0.1600 or less, or 0.1500 or less.
[0070] Furthermore, when the furnace atmosphere does not contain hydrogen, i.e., when the furnace atmosphere is an inert gas, if the dew point is too high, the decomposition of inhibitors such as AlN and (Al,Si)N is promoted, making secondary recrystallization unstable, so the dew point is set to 0°C or lower. Preferably, the dew point is set to -5°C or lower, or -10°C or lower. Furthermore, in order to form an SiO2 internal oxide layer on the steel sheet surface and further to form the internal oxide layer and the unevenness of the steel sheet surface to a predetermined size, the dew point is set to -20°C or higher, preferably -18°C or higher, -16°C or higher, or -15°C or higher.
[0071] <Annealing separator removal process> In the annealing separator removing step, the annealing separator is removed from the surface of the steel sheet after finish annealing (finish annealed steel sheet) by a method including one or both of water washing and pickling. If the excess annealing separator on the surface of the steel sheet is not sufficiently removed, the space factor deteriorates and the performance as an iron core decreases. In order to remove excess annealing separator, in addition to washing with water and pickling, a scrubber may be used to remove it. By using a scrubber, excess annealing separator that deteriorates wettability in the insulating coating application process can be reliably removed. When pickling is performed to remove excess annealing separator, it is preferable to use a solution containing one or more of sulfuric acid, nitric acid, hydrochloric acid, phosphoric acid, chloric acid, chromium oxide aqueous solution, chromium sulfuric acid, permanganic acid, peroxosulfuric acid, and peroxolinic acid in total at 20 wt% or less, preferably 10 wt% or less. By using such a solution, excess annealing separator on the steel sheet surface can be efficiently removed. Furthermore, when pickling is performed, the solution temperature is preferably set to 20 to 80° C. By setting the solution temperature within the above range, excess annealing separator on the steel sheet surface can be efficiently removed.
[0072] <Insulating film formation process> In the insulating coating formation process, an insulating coating is formed on the surface of the finish-annealed steel sheet after the annealing separator removal process. This insulating coating applies tension to the grain-oriented electrical steel sheet, thereby reducing the iron loss of the single steel sheet, and also ensures electrical insulation between the steel sheets when the grain-oriented electrical steel sheets are stacked for use, thereby reducing the iron loss of the iron core.
[0073] The type of insulating coating is not limited, but for example, an insulating coating liquid whose main component is at least one of phosphate and colloidal silica is applied, baked at 350 to 600°C, and then heat-treated at a temperature of 800 to 1000°C to form the insulating coating.
[0074] The colloidal silica is not particularly limited to colloidal silica having a specific property. The particle size is also not particularly limited to a specific particle size, but is preferably 200 nm (number average particle size) or less, for example, 5 to 30 nm. If the particle size exceeds 200 nm, it may precipitate in the coating liquid. The coating liquid may further contain chromic anhydride or a chromate. As the phosphate, a phosphate such as Ca, Al, or Sr is preferable, and among them, an aluminum phosphate is more preferable.
[0075] If the baking temperature of the insulating coating is too low, the insulating coating will drip during the running of the plate, causing poor appearance and not being able to obtain an insulating coating with sufficient adhesion, so it is set to 350°C or higher. It is preferably set to 370°C or higher, or 400°C or higher. If the baking temperature of the insulating coating is too high, the heating rate will be too fast, so only the outermost surface of the insulating coating will harden and the hardening of the inside will be delayed, causing poor coating formation and insufficient coating adhesion, so it is set to 600°C or lower. It is preferably set to 580°C or lower, 560°C or lower, or 540°C or lower. It is desirable to set the heating rate up to the baking temperature to 100°C / s or lower, preferably 70°C / s or lower, 50°C / s or lower, or 30°C / s or lower. By slowing down the heating rate during baking, the coating components can be sufficiently hardened.
[0076] For example, it is preferable to hold the temperature range of 350°C to 600°C for 2.5 seconds to 100 seconds. When hydrogen is contained in the furnace atmosphere, the oxidation degree in the atmosphere at this time may be 0.01 or more to form a SiO2 intermediate layer, but in order to form a sufficiently thick SiO2 intermediate layer, the oxidation degree during baking, for example, may be 1.00 or more, preferably 1.50 or more, 1.60 or more, 1.70 or more, 1.80 or more, 1.90 or more, or 2.00 or more. On the other hand, if the oxidation degree is too large, the SiO2 intermediate layer and internal oxidation in the steel sheet will proceed too much, so for example, the oxidation degree may be 4.00 or less, preferably 3.50 or less, or 3.00 or less. When hydrogen is not contained in the furnace atmosphere, the dew point temperature of the atmosphere may be 0°C to 50°C.
[0077] Furthermore, if the heat treatment temperature after baking is too low, poor film formation (insufficient hardening) occurs, resulting in insufficient film adhesion, so the heat treatment temperature after baking is set to 800°C or higher. Preferably, it is set to 820°C or higher, or 850°C or higher. Furthermore, if the heat treatment temperature after baking is too high, decomposition of the phosphate occurs, resulting in poor film formation and insufficient film adhesion, so the heat treatment temperature after baking is set to 1000°C or lower. Preferably, it is set to 970°C or lower, or 950°C or lower. The heat treatment temperature after baking is preferably maintained within a specified temperature range for 10 to 300 seconds.
[0078] When forming the coating, it is preferable to set the oxidation degree (PH2O / PH2) of the atmosphere in the heat treatment after baking to 0.01 to 1.50, since it is possible to form the insulating coating without decomposing the phosphate more than necessary. If the oxidation degree is too low, the SiO2 intermediate layer becomes thin, so the oxidation degree should be 0.01 or more, preferably 0.05 or more, 0.10 or more, 0.15 or more, or 0.20 or more. On the other hand, if the oxidation degree is too high, not only the SiO2 intermediate layer becomes too thick, but also the internal oxidation of the steel sheet progresses too much, so it is preferable to set the oxidation degree to 1.50 or less, preferably 1.40 or less, 1.20 or less, or 1.00 or less. In addition, it is preferable that the oxidation degree in the heat treatment after baking is lower than the oxidation degree during baking. The coating solution for forming an insulating coating can be applied to the surface of the steel sheet by a wet coating method such as a roll coater. As described above, it is preferable to apply the insulating coating so that the thickness becomes 3 to 30 μm.
[0079] The SiO2 intermediate layer formed between the base steel sheet and the insulating coating is formed during baking of the insulating coating and during the heat treatment after baking. Alternatively, the SiO2 intermediate layer may be formed on the surface of the base steel sheet by heat treatment before applying the coating liquid for the insulating film. In this case, the formation of the SiO2 intermediate layer and the formation of the insulating film are separate processes. If the SiO2 intermediate layer is not formed, the adhesion between the insulating coating and the base steel sheet cannot be ensured, and the insulating coating may peel off, which is undesirable.
[0080] When the insulating coating is cooled to room temperature after being formed by high-temperature heat treatment, it exerts tension on the steel sheet due to the difference in thermal expansion coefficient between the insulating coating and the base steel sheet. This can cause stress between the base steel sheet and the insulating coating, which can deteriorate the adhesion of the coating. On the other hand, in a heat-resistant magnetic domain-controlled grain-oriented electrical steel sheet in which a groove is provided on the base steel sheet, it is preferable to increase the tension on the base steel sheet because it can enjoy a greater magnetic domain control effect, but there is a problem that increasing the tension increases the possibility that the coating will peel off. The present inventors have found that even if a groove is provided on the base steel sheet by laser irradiation and the insulation coating tension is increased, the effect of suppressing the decrease in coating adhesion can be obtained by providing a SiO2 intermediate layer. Although the mechanism is not necessarily clear, it is presumed that the coating adhesion was improved on the surface on which the groove was formed due to the unevenness of the groove. On the other hand, it is presumed that the minute undulations of the steel sheet shape generated during laser irradiation contributed to the improvement of adhesion on the surface opposite to the groove formation.
[0081] <Magnetic domain control process> In this grain-oriented electrical steel sheet, a magnetic domain control process is provided in which a magnetic domain control process is performed either between the cold rolling process and the decarburization annealing process, between the decarburization annealing process (or the decarbonitriding process) and the annealing separator application process, between the annealing separator removal process and the insulating coating formation process, or after the insulating coating formation process. Magnetic domain control treatment can further reduce the core loss of grain-oriented electrical steel sheets by forming grooves on the surface of the steel sheet.
[0082] <How to form grooves> The method of forming the grooves is not particularly limited. Since mechanical methods such as pressing and rolling may cause deformation of the steel plate shape, it is preferable to adopt methods such as etching and laser. The groove formation method by laser irradiation will be described below.
[0083] <Laser irradiation conditions> By irradiating a cold-rolled steel sheet with a laser, multiple grooves are formed on the surface of the steel sheet in a direction intersecting the rolling direction such that the groove width W, groove depth D, and predetermined interval (groove interval P) fall within a specified range. Among the laser irradiation conditions, the type of laser light source, laser output, laser scanning speed, and steel sheet moving speed during laser irradiation are not particularly limited, but conditions may be appropriately selected such that the groove width W, groove depth D, and predetermined interval (groove interval P) fall within the specified range.
[0084] [Laser light source] As the laser light source, for example, a high-power laser generally used for industrial purposes such as a fiber laser, a YAG laser, a semiconductor laser, or a CO2 laser can be used. As long as the grooves can be stably formed, a pulsed laser or a continuous wave laser can be used.
[0085] [Laser output] If the laser output is less than 200W, the laser scanning speed to form the desired groove is significantly reduced, resulting in a reduction in industrial productivity, so it is preferable to set it to 200W or more. It is preferably 1000W or more, and more preferably 1500W or more. If the laser output is more than 3000W, the power supply capacity becomes large and the equipment cost becomes enormous, which is not industrially realistic, so it is preferable to set it to 3000W or less. It is preferably 2800W or less, and more preferably 2500W or less.
[0086] [Laser scanning speed] When the laser scanning speed is less than 5 m / s, the steel sheet passing speed must be slowed down, resulting in reduced productivity, and therefore the speed is set to 5 m / s or more. It is preferably set to 20 m / s or more, and more preferably set to 40 m / s or more. When the laser scanning speed is faster than 100 m / s, a higher output is required, which increases the equipment cost, and therefore the speed is set to 100 m / s or less. It is preferably set to 80 m / s or less, and more preferably set to 60 m / s or less.
[0087] [Laser light focusing spot shape] The shape of the focused spot of the laser light is not particularly limited. It is preferable that the shape is circular or elliptical on the surface of the base steel sheet. To prevent the spot from spreading too much, for example, the ratio (dL / dC) of the focused spot diameter dL of the laser light in the rolling direction to the focused spot diameter dC of the laser light in the sheet width direction should satisfy 0.01 to 100.
[0088] <Assist gas> Simultaneously with the irradiation of the laser light, an assist gas may be sprayed onto the portion of the steel sheet to be irradiated with the laser light. The assist gas plays a role in removing components melted or evaporated from the steel sheet by the laser irradiation. By spraying the assist gas, the laser light reaches the steel sheet stably, so that grooves are formed stably. The flow rate of the assist gas is preferably, for example, 10 to 1000 liters per minute. The assist gas is preferably air or an inert gas. EXAMPLES
[0089] <Example 1> A slab containing 3.3 mass% Si, 0.10 mass% Mn, 0.006 mass% S, 0.060 mass% C, 0.027 mass% acid-soluble Al, 0.008 mass% N, and the remainder being Fe and impurities, was hot-rolled by a known method, annealed as a hot-rolled sheet, and cold-rolled to a final thickness of 0.22 mm to obtain steel sheets A1 to A12 and a1 to a12.
[0090] Next, in A1 to A12 and a5 to a12, the cold-rolled steel sheets were decarburized and then subjected to nitriding treatment. The decarburization conditions were to heat up to 850°C, hold for 60 seconds, and then cool. The decarburization atmosphere was a hydrogen-nitrogen atmosphere, with PH2O / PH2 at 0.1. The amount of nitriding was 200 ppm. In addition, in a1 to a4, the cold-rolled steel sheets were decarburized and then subjected to nitriding treatment. The decarburization conditions were to heat up to 850°C, hold for 60 seconds, and then cool. The decarburization atmosphere was a hydrogen-nitrogen atmosphere, with PH2O / PH2 at 0.3. The amount of nitriding was 200 ppm.
[0091] Then, for A1 to A12 and a5 to a12, an annealing separator mainly composed of alumina (Al2O3) with MgO / (MgO+Al2O3) of 40% was applied at a coating amount of 4 g / m on one side. 2 In a1 to a4, magnesia (MgO) was used as an annealing separator, and the coating amount was 4 g / m on one side. 2 The coating was applied so that the result was as follows.
[0092] Next, the steel sheet was wound into a coil and held at a maximum temperature of 1200°C for 20 hours in a nitrogen atmosphere containing 5% hydrogen, and then cooled to obtain a finish annealed sheet. The oxidation degree PH2O / PH2 in the temperature range of 800°C to 900°C during the temperature rise process of the finish annealing was set to 0.010. After that, excess annealing separator was removed from the surface of the steel sheet.
[0093] Next, a water-based coating solution (insulating film forming solution) mainly composed of phosphate and colloidal silica was applied to the steel sheet, and the steel sheet coated with the insulating film forming solution was heated to 500°C at a heating rate of 20°C / s in an atmosphere adjusted to a furnace oxidation degree (PH2O / PH2) of 2.00, and the insulating film was baked and hardened. The steel sheet was then baked and annealed (soaked) at 850°C to form an insulating film. In this example, aluminum phosphate was used, and the particle size of the colloidal silica (average particle size based on number) was 100 nm. The furnace oxidation degree (PH2O / PH2) during the baked and annealed process was adjusted to 1.00. The thickness of the insulating film was measured after film formation. The specifications of the insulating film are shown in Table 1.
[0094] As a magnetic domain control process, grooves were formed by etching or laser either between the cold rolling process and the decarburization annealing process, between the decarburization annealing process and the annealing separator application process, between the annealing separator removal process and the insulating film formation process, or after the insulating film formation process. The specifications of the grooves are shown in Table 1.
[0095] For A1 to A12 and a1 to a12, the iron loss W17 / 50 (energy loss measured under excitation conditions of 1.7 T and 50 Hz) was measured. The results are shown in Table 1.
[0096] [Table 1]
[0097] In Examples A1 to A12 and Comparative Examples a1 to a8, the conditions of groove angle, groove depth, groove interval, and groove width that affect iron loss are all the same, and the magnetic flux density is all about the same, while the iron loss of Examples A1 to A12 is less than 0.600 W / kg, which is good. The coating tension at that time was 10 MPa or more in all cases.
[0098] Comparative Examples a1 to a4 were grain-oriented electrical steel sheets having a glass coating, the coating tension was 10 MPa or more, and the groove shape was the same as that of Invention Examples A1 to A12, but the iron loss was higher and inferior to that of the Invention Examples.
[0099] <Example 2> A slab containing 3.3 mass% Si, 0.10 mass% Mn, 0.006 mass% S, 0.060 mass% C, 0.027 mass% acid-soluble Al, 0.008 mass% N, and the remainder being Fe and impurities, was hot-rolled by a known method, annealed as a hot-rolled sheet, and cold-rolled to a final thickness of 0.22 mm to obtain steel sheets B1 to B12.
[0100] Next, the cold-rolled steel sheet was decarburized and then subjected to nitriding treatment. The decarburization conditions were to heat up to 850°C, hold for 60 seconds, and then cool. The decarburization atmosphere was a hydrogen-nitrogen atmosphere with a PH2O / PH2 ratio of 0.1. The amount of nitriding was 200 ppm.
[0101] After that, an annealing separator mainly made of alumina (Al2O3) with MgO / (MgO+Al2O3) of 40% was applied to each side at a rate of 4g / m 2 The coating was applied so that the result was as follows.
[0102] Next, the steel sheet was wound into a coil and held at a maximum temperature of 1200° C. for 20 hours under the same conditions as in Example 1, and then cooled to obtain a finish-annealed sheet.
[0103] Furthermore, an insulating coating was formed in the same manner as in Example 1. The specifications of the insulating coating are shown in Table 2.
[0104] In the grain-oriented electrical steel sheet according to this embodiment, grooves were formed by etching or laser either between the cold rolling process and the decarburization annealing process, or between the decarburization annealing process and the annealing separator application process. The specifications of the grooves are shown in Table 2.
[0105] For B1 to B12, the iron loss W17 / 50 (energy loss measured under excitation conditions of 1.7 T and 50 Hz) was measured. The results are shown in Table 2.
[0106] [Table 2]
[0107] Inventive Examples B1 to B12, the iron loss was less than 0.550 W / kg, which was even better. The coating tension at this time was 10 MPa or more, the absolute value of the angle θ formed with the longitudinal direction of the groove was 0 to 40°, the width W of the groove was 20 to 300 μm, the depth D of the groove was 10 to 50 μm, and the interval P of the groove in the rolling direction was 1 to 30 mm.
[0108] <Example 3> The slabs contained 3.3 mass% Si, 0.10 mass% Mn, 0.006 mass% S, 0.060 mass% C, 0.027 mass% acid-soluble Al, 0.008 mass% N, and the remainder Fe and impurities. The slabs were hot-rolled by a known method, annealed as hot-rolled sheets, and cold-rolled to a final thickness of 0.22 mm to obtain steel sheets C1 to C16.
[0109] Next, the cold-rolled steel sheet was decarburized and then subjected to nitriding treatment. The decarburization conditions were to heat up to 850°C, hold for 60 seconds, and then cool. The decarburization atmosphere was a hydrogen-nitrogen atmosphere with a PH2O / PH2 ratio of 0.1. The amount of nitriding was 200 ppm.
[0110] After that, an annealing separator mainly made of alumina (Al2O3) with MgO / (MgO+Al2O3) of 40% was applied to each side at a rate of 4g / m 2 The coating was applied so that the result was as follows.
[0111] Next, the steel sheet was wound into a coil and held at a maximum temperature of 1200° C. for 20 hours under the same conditions as in Examples 1 and 2, and then cooled to obtain a finish-annealed sheet.
[0112] Furthermore, an insulating coating was formed in the same manner as in Examples 1 and 2. The specifications of the insulating coating are shown in Table 3.
[0113] In the grain-oriented electrical steel sheet according to this embodiment, grooves were formed by etching or laser either between the cold rolling process and the decarburization annealing process, between the decarburization annealing process and the annealing separator application process, between the annealing separator removal process and the insulating coating formation process, or after the insulating coating formation process. The specifications of the grooves are shown in Table 3.
[0114] For C1 to C16, the iron loss W17 / 50 (energy loss measured under excitation conditions of 1.7 T and 50 Hz) was measured. The results are shown in Table 3.
[0115] [Table 3]
[0116] Inventive Examples C1 to C16, the core loss is less than 0.600 W / kg, which is favorable. [Industrial Applicability]
[0117] The present invention can be used in industrial equipment that uses grain-oriented electrical steel sheets, such as winding cores for transformers. [Explanation of symbols]
[0118] 1 steel plate 2 grooves Θ Groove angle W groove width D Groove Depth d Groove Spacing 10 Base steel plate 11 Internal oxide layer 12 SiO2 intermediate layer 13 Insulation coating 14 Concave / convex height 15 Interface curve 16 Line connecting the ends of the interface curves on the steel plate surface side 17 Line connecting the ends of the interface curves on the steel plate center side
Claims
1. The steel plate has a plurality of grooves on the surface thereof, On the surface of the steel sheet, which is the base material, SiO 2 The insulating coating has an intermediate layer and SiO 2 as a main component. No forsterite coating, The base steel sheet has an SiO 2 internal oxide layer directly beneath the surface thereof, In a cross section in the thickness direction of the steel plate, the unevenness height of the interface between the SiO 2 internal oxidation layer and the steel plate serving as the base material is 0.001 μm or more and 0.100 μm or less in the thickness direction of the steel plate, The coating tension of the insulating coating is 10 MPa or more. A directional electrical steel sheet.
2. The angle θ between the direction perpendicular to the rolling direction and the plate thickness direction of the steel plate and the longitudinal direction of the groove is 40° or less; The width W of the groove is 20 to 300 μm, The depth D of the groove is 10 to 50 μm; The interval P of the grooves in the rolling direction is 1.0 to 30.0 mm The grain-oriented electrical steel sheet according to claim 1 .
Citation Information
Patent Citations
Method for improving magnetostriction of oriented silicon steel sheet by laser nicking decarburized plate
CN114561512A
JP1974096920A
Portable receiver
JP1987053579A
Formation of insulated film on grain-oriented silicon steel sheet
JP1994184762A
Production of mirror-finished grain-oriented selicon steel sheet low in core loss
JP1996003648A